Challenges and Drivers of Industrialist Propensity Among Chemical Engineering Students in STEM Institution in Zimbabwe: Towards A Conceptual Framework - Nkala, Bongani; Sibanda, Victor M.; Ndhlovu, Jacqueline; Hobane, Lungile; Singh, Shamila (Three E Science Institute, 2024)
NUST in Zimbabwe grapples with a significant challenge. Despite enrolling many students in chemical engineering, the nation lacks operational industries. Consequently, graduates often encounter difficulties securing employment or attachment placements post-graduation. This underscores the critical need to foster student entrepreneurship, encouraging innovation and idea generation. The study employed a mixed-methods research design to address this issue, combining qualitative and quantitative methodologies. The quantitative aspect utilized a quasi-experimental pre-test and post-test design, while the qualitative component involved conducting focus group interviews with chemical engineering students in the experimental group. The findings from both approaches complemented each other, providing a comprehensive understanding of the factors influencing entrepreneurial propensity among NUST chemical engineering students. Data collection involved distributing research instruments and questionnaires to NUST students and individuals associated with the mining and pharmaceutical industries. The collected data were then entered into an Excel spreadsheet, allowing for the recording of respondents' numbers alongside their respective responses. The study applied descriptive statistics to evaluate responses and their alignment with research objectives, revealing barriers to entrepreneurial inclination among NUST chemical engineering students, such as limited resources, risk aversion, inadequate entrepreneurial education, and cultural norms. Students benefited from personal motivation, a supportive educational atmosphere, networking opportunities, and exposure to innovative ideas. These factors nurtured self-determination, social networking, and an entrepreneurial mindset. To foster entrepreneurial spirit among NUST chemical engineering students, the study suggests educational reforms, mentorship programs, and potential policy changes create an enabling environment, empowering students to pursue entrepreneurship and contribute to economic growth.